2007
DOI: 10.3171/jns.2007.106.5.855
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and endovascular management of symptomatic posterior circulation fusiform aneurysms

Abstract: Certain posterior circulation aneurysm locations (PCA, VA-PICA, and BA-VBJ) represent separate disease entities affecting patients at different ages with distinct patterns of presentation, treatment options, and outcomes. Favorable overall long-term outcome can be achieved in 90% of patients with PCA aneurysms, in 60% of those with VA-PICA aneurysms, and in 39% of those with BA-VBJ aneurysms when using endovascular and surgical techniques. The natural history of the disease was poor in patients with incomplete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 26 publications
(40 reference statements)
1
71
0
8
Order By: Relevance
“…Fusiform aneurysms are not considered in this study given how different their pathology and morphology are from that of saccular aneurysms. 3 The distribution of the aneurysms according to their location, rupture status, and relation with parent vessel is shown in Table 1 together with the mean values of their largest diameter size derived from manual measurements in 3D space. The average maximal size of the aneurysms in the database is 6.8 ± 3.1 mm.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Fusiform aneurysms are not considered in this study given how different their pathology and morphology are from that of saccular aneurysms. 3 The distribution of the aneurysms according to their location, rupture status, and relation with parent vessel is shown in Table 1 together with the mean values of their largest diameter size derived from manual measurements in 3D space. The average maximal size of the aneurysms in the database is 6.8 ± 3.1 mm.…”
Section: Data Descriptionmentioning
confidence: 99%
“…When surgical clipping is performed, there are some risks of neurological complications because of the intimate anatomical relationships of the proximal PICA to the brain stem and lower cranial nerves 2,4,11) . Because of difficulty in general anesthesia due to poor general condition, recent advancement in endovascular surgery, and difficulties related with surgery, endovascular treatment is being used as a primary or alternative method for treating these aneurysms 3,6) . For ruptured or unruptured PICA aneurysms, in our knowledge, many authors 2,4,7,8,14,15) reported the clinical outcomes of surgery or endovascular treatment, but there was only one Results : Eleven (55%) and nine (45%) patients were treated with surgical clipping and endovascular treatment, respectively.…”
mentioning
confidence: 99%
“…Оптимальный способ лечения подобных аневризм остается неопределен-ным вследствие их парастволовой локализации, на-личия широкой шейки, кальцификации стенок и плотности внутриартериальных тромбов. Для пред-отвращения ишемических нарушений важным яв-ляются сохранение тонких перфорирующих вето-чек, исходящих из шейки аневризмы к стволу голов-ного мозга, уменьшение размеров аневризмы и ре-васкуляризация гемодинамически значимых ветвей несущего сосуда, подвергающегося микрохирурги-ческому или эндоваскулярному выключению [2,4,13,[18][19][20][21][22][23].…”
Section: Discussionunclassified
“…Увеличение размеров аневризмы вследствие постепенного тром-бообразования сопровождается разнообразными неврологическими проявлениями в результате пря-мого воздействия на продолговатый мозг и крани-альные нервы, развитием окклюзионной гидроце-фалии в результате обструкции IV желудочка, а так-же ишемическими поражениями ствола головного мозга, вызванными нарушением кровообращения в сдавленных перфорирующих сосудах [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: список сокращенийunclassified